2015
DOI: 10.1371/journal.pone.0128582
|View full text |Cite
|
Sign up to set email alerts
|

Fructose Levels Are Markedly Elevated in Cerebrospinal Fluid Compared to Plasma in Pregnant Women

Abstract: BackgroundFructose, unlike glucose, promotes feeding behavior in rodents and its ingestion exerts differential effects in the human brain. However, plasma fructose is typically 1/1000th of glucose levels and it is unclear to what extent fructose crosses the blood-brain barrier. We investigated whether local endogenous central nervous system (CNS) fructose production from glucose via the polyol pathway (glucose→sorbitol→fructose) contributes to brain exposure to fructose.MethodsIn this observational study, fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 38 publications
5
19
0
Order By: Relevance
“…Furthermore, the production of sorbitol and fructose was blocked by sorbinil, an inhibitor of the rate-limiting enzyme, aldose reductase (26). Together with the previous finding that fructose and sorbitol are present in human cerebrospinal fluid at markedly higher concentrations than in the periphery (12,14,27), the present observations suggest that endogenous human brain fructose production may be a key underappreciated factor modulating ingested sugar's effect on the brain. While it is possible that plasma fructose may cross the BBB, we observed that the rise of intracerebral fructose occurred much earlier (by 20 minutes) than the modest increase in peripheral fructose levels (at 180 minutes).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Furthermore, the production of sorbitol and fructose was blocked by sorbinil, an inhibitor of the rate-limiting enzyme, aldose reductase (26). Together with the previous finding that fructose and sorbitol are present in human cerebrospinal fluid at markedly higher concentrations than in the periphery (12,14,27), the present observations suggest that endogenous human brain fructose production may be a key underappreciated factor modulating ingested sugar's effect on the brain. While it is possible that plasma fructose may cross the BBB, we observed that the rise of intracerebral fructose occurred much earlier (by 20 minutes) than the modest increase in peripheral fructose levels (at 180 minutes).…”
Section: Discussionsupporting
confidence: 77%
“…When considered with our recent finding that plasma fructose levels are only 0.1% of plasma glucose levels, compared with CSF in which fructose is 6%-7% of glucose (28), these findings suggest that relative changes in brain fructose may be greater than relative changes in brain glucose levels, potentially making fructose a highly sensitive neuronal signal for carbohydrate ingestion. Interestingly, in Drosophila, any nutritious carbohydrate ingestion results in increased hemolymph fructose levels (through the polyol pathway), which in turn acts on a nutrient sensor in the fruit fly brain (29).…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Physiologically, endogenously synthesized fructose is the primary energy source for sperm and may be important for fertility (104)(105)(106). The placenta may also synthesize sorbitol that the developing fetus may use to synthesize fructose, suggesting a broader role for endogenous fructose in reproductive and developmental biology (107).…”
Section: Endogenous Fructose Productionmentioning
confidence: 99%
“…Despite the low concentration of fructose in the plasma, fructose has a potential to generate AGEs more readily than the same amount of glucose; in addition, it generates pre-AGE carbonyl compounds, such as glyceraldehyde and methylglyoxal 71 . Moreover, in cerebrospinal fluid (CSF), fructose concentration may be controlled by a mechanism that is distinct from that of the plasma, as fructose levels are increased and glucose levels are decreased in this compartment compared with the plasma 70,72 . Fructose-derived pre-AGE carbonyl compounds were detoxified by GLO1 quickly in astrocytes in wild-type mice and probably even in Glo1 heterozygous mice, because of its strong expression in these cells.…”
Section: Discussionmentioning
confidence: 99%